Fabrication of Poly(vinyl alcohol)/Chitosan Composite Films Strengthened with Titanium Dioxide and Polyphosphonate Additives for Packaging Applications - Tăchiță Vlad-Bubulac; Corneliu Hamciuc; Cristina Mihaela Rîmbu; Magdalena Aflori; Maria Butnaru; Alin Alexandru Enache; Diana Serbezeanu (Gels, 2022)
Eco-innovation through the development of intelligent materials for food packaging is evolving, and it still has huge potential to improve food product safety, quality, and control. The design of such materials by the combination of biodegradable semi-synthetic polymers with natural ones and with some additives, which may improve certain functionalities in the targeted material, is continuing to attract attention of researchers. To fabricate composite films via casting from solution, followed by drying in atmospheric conditions, certain mass ratios of poly(vinyl alcohol) and chitosan were used as polymeric matrix, whereas TiO2 nanoparticles and a polyphosphonate were used as reinforcing additives. The structural confirmation, surface properties, swelling behavior, and morphology of the xerogel composite films have been studied. The results confirmed the presence of all ingredients in the prepared fabrics, the contact angle of the formulation containing poly(vinyl alcohol), chitosan, and titanium dioxide in its composition exhibited the smallest value (87.67°), whereas the profilometry and scanning electron microscopy enlightened the good dispersion of the ingredients and the quality of all the composite films. Antimicrobial assay established successful antimicrobial potential of the poly(vinyl alcoohol)/chitosan-reinforced composites films against Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Pseudomonas aeruginosa, and Candida albicans. Cytotoxicity tests have revealed that the studied films are non-toxic, presented good compatibility, and they are attractive candidates for packaging applications.